Discovering EFL Learners’ Perspectives in Unscripted Role-Play - Salsabila, Nada; Megawati, Fika (Journal of English for Academic and Specific Purposes (JEASP), 2024)
This research emphasized the value of interactive activities, especially unscripted role-play, in improving Indonesian EFL learners' spontaneous English speaking skills in their learning. By exploring learners' experiences in script-free role-playing, the study contributes valuable insights into the importance of active language practice in language learning, emphasizing practical communication skills over theoretical knowledge. The purpose of this study is to give an overview of effective language teaching approaches that enhance the fluency and spontaneous English expression of Indonesian as English Foreign Language (EFL) Learners. Through qualitative methods, including observation notes, reflective surveys, and interviews, the research aimed to provide a comprehensive perspective on how EFL learners perceive spontaneity in unscripted role-play activities. The findings are expected to broaden the understanding of EFL learners' experiences in engaging in script-free role-playing. By addressing the challenges learners face in mastering spontaneous English conversations and the importance of active language practice, the study contributes to the discourse on effective language teaching strategies.